ALTERATION: 2013 CURRICULUM BECOMES MERDEKA CURRICULUM IN ELEMENTARY SCHOOLS - Handara Tri Elitasari; Yeni Rakhmawati; Irma Yulianti Budi Safitri; Muhammad Asip (PROGRES PENDIDIKAN, 2023)
The implementation of the 2013 curriculum in elementary schools had not been able to answer the problems of education in Indonesia. The results of the Pisa Indonesia test scores did not show a significant increase in scores, strengthening and instilling character values that matched expectations, as well as loss of learning experienced by students during the COVID-19 pandemic. It was important to make changes to improve the curriculum. The type of research used was a literature review. The stages carried out in this literature review include the search for related articles, filtering the content of articles that were in accordance with the article to be created, and synthesis of article content. The 2013 curriculum had not been able to accommodate the needs of learning about literacy and character which are important needs today. Thus, an adequate curriculum framework was needed and in accordance with the needs of students, so that students get the right to learn as a whole. Therefore, the independent curriculum provides solutions through independent learning programs and driving teacher programs that teachers hope to create creative and innovative learning, understand the learning needs of students, be technologically literate, and could create a democratic environment